(untitled) (Baghdad Science Journal, 2015)
Reproduction potential and age –specific fecundity of the Mealybug Planococcus citri Risso were studied in the laboratories of Biological control research unit,college of Agriculture –Baghdad university at 25± 2Cº and 60-70% R.H.with 16 light:8 dark photo period.The results showed that the survival ratio began to decline at the 38th day, the average female age was 20 days ,while the average age was 8 days at the first reproduction . Net reproduction rate ( Ro ) was 58.59 female female generation which prove that the population of the mealybug was of the unstable kind , intrinsic rate of increase (rm) was 0.118 femalefemale and the average length period of generation ( T ) was 34.30 days . Many local predators attack the mealybug such as two species of chrysopid ,Chrysoperla carnea and C.mutata and the Dipterian predator Dicrodiplosis manhoti. Also more than 10 coccinellid predators, such as, Nephus jaderiensis , Scymnus syriacus , coccinella septempunctata and C.undecimipunctata .This predators play important role as a bio-control agents to decline the population densities of mealybug naturally in IRAQ .